Mind power : into the 21st century - Kehoe, John (Canada : Zoetic Inc., 1996)
'John Kehoe has articulated a set of life-changing principles for charting a course to success and happiness' from the back cover.
'Techniques to harness the astounding powers of thought'-- Cover.
Book is accompanied by one computer optical disc entitled'The complete mind power home study course' bearing the same call number and available at Bahagian Koleksi Media.
Includes bibliographical references (p. [147]-148).
Keywords: Mental suggestion; Thought and thinking; Subconsciousness; Mental healing; Success -- Psychological aspects